2003
DOI: 10.3727/000000003783985179
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Hepatocyte-Like Cells from Human Embryonic Stem Cells

Abstract: Use of human hepatocytes for therapeutic and drug discovery applications is hampered by limited tissue source and the inability of hepatocytes to proliferate and maintain function long term in vitro. Human embryonic stem (hES) cells are immortal and pluripotent and may provide a cell source for functional human hepatocytes. We report here that hES cells can be induced to differentiate into hepatocyte-like cells. Treatment with sodium butyrate induced hepatic differentiation as well as significant cell death, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
269
0
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(282 citation statements)
references
References 35 publications
5
269
0
4
Order By: Relevance
“…2D-F), but not AFP ( Fig. 2A-C), which was consistent with the process previously described [Rambhatla et al, 2003]. After removal of sodium butyrate, the granular-rich large cells changed into ES-derived hepatic progenitor cells accompanied with the increased expression of AFP and decreased expression of ALB until undetectable with immunofluorescence ( Fig.…”
Section: Identification and Characterization Of Es-derived Hepatic Prsupporting
confidence: 90%
See 1 more Smart Citation
“…2D-F), but not AFP ( Fig. 2A-C), which was consistent with the process previously described [Rambhatla et al, 2003]. After removal of sodium butyrate, the granular-rich large cells changed into ES-derived hepatic progenitor cells accompanied with the increased expression of AFP and decreased expression of ALB until undetectable with immunofluorescence ( Fig.…”
Section: Identification and Characterization Of Es-derived Hepatic Prsupporting
confidence: 90%
“…The treated cells exhibited morphological features of primary hepatocytes and expressed liver-associated genes and proteins. In addition, the majority of the treated cells remained in cell cycle for 3 days after the addition of sodium butyrate, but the cycling fraction decreased to 17% 7 days later [Rambhatla et al, 2003]. It was now established that treatment of cells both in vitro and in vivo with sodium butyrate, a potential histone deacetylase (HDAC) inhibitor, could result in specific functional outcomes such as proliferation, cell cycle arrest, apoptosis, or differentiation [Janson et al, 1997;Sambucetti et al, 1999;Wang et al, 1999;Travers et al, 2002;Camphausen et al, 2004;Hsieh et al, 2004;Bug et al, 2005;Cho et al, 2005;Jiang et al, 2005;Rossig et al, 2005].…”
mentioning
confidence: 99%
“…The recent report of a technique for efficient generation of definitive endoderm from ES cells by culture in lower concentrations of serum and Activin A [7][8][9] has been an important advance for subsequent production of hepatocyte-like cells. We have found that induction of definitive endoderm from ES cells was a necessary step for subsequent hepatic differentiation in vitro.…”
Section: Protocols Have Been Developed To Differentiate and Enrich Vamentioning
confidence: 99%
“…In addition, the hepatic-like cells were suggested to develop in a niche next to cardiac mesodermal cells and that aFGF may play a role in this differentiation. The differentiation towards hepatic-like cells were also demonstrated by using other factors [Rambhatla et al, 2003;Shirahashi et al, 2004]. Shirahashi et al [2004], added insulin and dexamethasone to EBs cultured on collagen type I and showed that the cells express various endodermal genes.…”
Section: Embryonic Stem Cells and Hepatocytesmentioning
confidence: 94%
“…Shirahashi et al [2004], added insulin and dexamethasone to EBs cultured on collagen type I and showed that the cells express various endodermal genes. Rambhatla et al [2003], added sodium butyrate to the culture media inducing hepatic differentiation as well as significant cell death. The resultant cells had morphological features similar to that of primary hepatocytes and most of the cells expressed liver associated proteins.…”
Section: Embryonic Stem Cells and Hepatocytesmentioning
confidence: 99%